C# 7 and .NET Core modern cross-platform development : create powerful cross-platform applications using C# 7, .NET Core, and Visual Studio 2017 or Visual Studio Code /: create powerful cross-platform applications using C# 7, .NET Core, and Visual Studio 2017 or Visual Studio Code. (2017) - Price, Mark J
No abstract available